Strategic surface modification of ZnO interlayer for optimizing power conversion efficiency of solar cells based on quinoxaline-based polymer - Jeon, Gyeong G.; Lee, Seok Woo; Eun, Hyeong Ju; Kim, Jincheol; Chang, Dong Wook; Kim, Jong H. (Dyes and Pigments, 2022)
A new quinoxaline-based conjugated donor polymer (PQTBDT), comprising an electron-donating benzodithiophene unit and electron-accepting cyanoquinoxaline was synthesized for bulk heterojunction-type polymer solar cell applications. The effects of morphology and solvent treatment of ZnO interlayer on the photovoltaic properties of PQTBDT-based PSCs were investigated through systemic characterization of morphology, UV–Vis absorption, transmittance, and charge recombination properties. Nano-ripple-structured ZnO electron transport layer enhanced both charge extraction capability and short circuit current density by enlarged interface contact area and light trapping effect, respectively. Additional solvent treatment using ethanolamine further reduced interface charge traps, resulting in higher shunt resistance compared to the devices based on planar ZnO layer. Combination of these two processes for ZnO interlayer optimized performance of PQTBDT-based solar cells with power conversion efficiency up to 6.50%.
Keywords: Benzodithiophene; Cell-based; Electron-donating; Power conversion efficiencies; Quinoxaline polymer; Quinoxalines; Recombination; Solvent treatment; Surface-modification; ZnO interlayers; Morphology; Polymer solar cells; Quinoxaline polymer; Recombination; Zinc oxide